Michael Vey: The Final Spark - Book 7 - Evans, Richard Paul (New York : Mercury Ink/Simon Pulse, 2017)
"The final book in the Michael Vey series-- Michael is missing. The battle on the island of Hades ended with a devastating explosion that left the island a smoking ruin and much of Hatch's army dead. However, Hatch survived and while his plans have certainly suffered a setback, he's more determined than ever to bring the world's governments under his control. But first, he wants to wipe out the Resistance and capture the remaining members of the Electroclan. As Hatch's forces storm into action, it seems nothing can stand in their way. The Electroclan is divided. The voice is captured, and Michael's mother is being used as bait to lure the leader of the Resistance out of hiding. Can anything--or anyone--stop the Elgen? Or is this the end?"--
Keywords: Vey, Michael -- Juvenile fiction; Vey, Michael -- Fiction; Teenagers -- Juvenile fiction; Missing persons -- Juvenile fiction; Friendship in adolescence -- Juvenile fiction; Electricity -- Juvenile fiction; Tourette syndrome -- Juvenile fiction; Teenagers -- Fiction; Missing persons -- Fiction; Friendship -- Fiction; Electricity -- Fiction; Tourette syndrome -- Fiction; Science fiction